Immature defense mechanisms and suicide attempts in borderline personality organization: a clinical sample study - Şahin, Ardil Bayram; Giousouf Chousein, Mourat; Uludağ, Doruk; Saydam, M. Bilgin (Frontiers in Psychology, 2025)
ObjectiveThis study aimed to investigate the relationship between defense mechanisms and suicide attempts in individuals with borderline personality organization (BPO), considering the high prevalence of suicide attempts in this population.MethodsA total of 80 participants (71.25% female) who met all inclusion criteria and had complete data were included in the analyses. They were recruited from the outpatient psychotherapy unit of a university hospital. All participants participated in clinical interviews and completed standardized psychometric scales, including the Borderline Personality Inventory (BPI), Defense Style Questionnaire, and Symptom Checklist-90 Revised (SCL-90-R). Participants were classified two group based on their history of suicide attempts. Statistical analyses, including group comparisons, correlation analyses, and regression models, were used to explore the relationship between defense mechanisms and suicide attempts among individuals with BPO.ResultsOf the 80 participants (57 females, 23 males; mean age = 26.7, SD = 7.7), 23 reported at least one suicide attempt, while 57 had no suicide attempt history. Suicide attempters exhibited significantly higher scores on the BPI and immature defense mechanisms, particularly projection, acting out, and splitting (all p < 0.05). Correlation analyses revealed significant positive relationships between BPI and immature defense style (r = 0.55, p < 0.001), particularly splitting (r = 0.46, p < 0.001), projection (r = 0.43, p < 0.001), autistic fantasy (r = 0.41, p < 0.001), and acting out (r = 0.31, p < 0.001). Regression analyses were conducted using two models. The first model included age, sex, and the three defense styles (mature, neurotic, and immature) as independent variables. The second model included age, sex, and 20 individual defense mechanisms as independent variables. In the first model, immature defenses (OR = 1.035, p = 0.014) and female sex (OR = 4.968, p = 0.032) were significantly associated with history of suicide attempt. In the second model, the projection defense mechanism (OR = 1.224, p = 0.006) and female sex (OR = 4.071, p = 0.048) were significantly associated.ConclusionThese findings emphasize the importance of specific immature defense mechanisms, such as projection, and female sex, in understanding suicide attempts in individuals with BPO. Future research should investigate whether therapeutic modification of these defenses may reduce suicidality and improve outcomes.